COMMUNITY COLLABORATION FOR SUSTAINABLE PEACE-BUILDING BETWEEN FARMERS AND HERDERS IN PLATEAU STATE, NIGERIA - Gukas, Theophilus (FUDMA JOURNAL OF SCIENCES, 2025)
The persistent conflict between farmers and herders in Plateau State, Nigeria, has escalated into a major security and socio-economic crisis, driven by resource competition, historical grievances, religious polarization, and governance failures. This study examines community perspectives on reconciliation, confidence-building, and dispute resolution to identify viable strategies for fostering peace. Using a mixed-method approach, data were collected from farming and herding communities through structured surveys, interviews, and focus group discussions. The findings reveal a significant disparity in willingness to engage in dialogue, with herders demonstrating a higher openness to reconciliation compared to farmers, who remain deeply distrustful due to past grievances. Land disputes (79.4%) and water scarcity (69.6%) emerge as the primary causes of conflict, while lack of trust (79.6%) and fear of attack (69.4%) are identified as major barriers to peace. Despite these challenges, there is strong community support for interfaith dialogues (79.8%), joint economic projects (70.2%), and hybrid dispute resolution mechanisms that integrate both traditional and formal legal systems. The study shows the need for trauma healing programs, youth engagement initiatives, and livelihood support as essential components of sustainable peacebuilding. The findings contribute to existing literature by providing empirical insights into grassroots attitudes toward reconciliation and highlight the importance of culturally sensitive, community-driven approaches in addressing farmer-herder conflicts. By prioritizing trust-building, inclusive dialogue, and economic cooperation, locally led peace initiatives can pave the way for long-term conflict transformation and coexistence in Plateau State.